Integrative Transcriptomic, Lipidomic, and Metabolomic Analysis Reveals Potential Biomarkers of Basal and Luminal Muscle Invasive Bladder Cancer Subtypes - Feng, Chao; Pan, Lixin; Tang, Shaomei; He, Liangyu; Wang, Xi; Tao, Yuting; Xie, Yuanliang; Lai, Zhiyong; Tang, Zhong; Wang, Qiuyan; Li, Tianyu (Frontiers in Genetics, 2021)
Muscle invasive bladder cancer (MIBC) is a heterogeneous disease with a rate of recurrence and poor clinical outcome. The establishment of basal and luminal MIBC subtypes provides a foundation for exploring MIBC intertumoral heterogeneity. Lipidomics and metabonomics have greatly aided progress in cancer research but the lipid and metabolite profiles of basal and luminal MIBC subtypes have not been studied to date. Here, we divided MIBC patients into basal and luminal subtype groups via a MIBC classifier based on transcriptome expression profiles. We qualitatively and quantitatively analyzed the lipidomic and metabonomic landscapes of basal and luminal MIBC subtypes, and revealed the differential lipid and metabolite profiles. Our results suggest that free fatty acids (FFA) and sulfatides (SL), which are closely associated with immune and stromal cell types, have strong capacities to distinguish basal and luminal subtypes of MIBC tumors. Moreover, our results show that the ratios of glycerophosphocholine (GCP)/imidazoles and nucleosides/imidazoles can accurately identify tumors of basal and luminal MIBC subtypes. Our study integrates transcriptomic, lipidomic, and metabolomic data to reveal the differential lipids and metabolites in basal and luminal MIBC subtypes, and provides biomarkers for precision therapy of basal and luminal subtypes in MIBC.